APPLIED STUDY OF SUSTAINABLE ARCHITECTURE CONCEPT AT PACIFIC PLACE MALL JAKARTA - Rahim, Putri Adelia Purwidya; Cahyani, Fadhilah Putri; Winarto, Erwin Djuni; Mutia, Fairuz (ADBE, 2023)
In recent years, global warming has been intensively discussed internationally. Global warming had led to the rise of the concept of green architecture to minimize energy use, building maintenance, and create a comfortable and healthy environment. Green Architecture concept is usually based on principles in accordance with GBCI (Green Building Council Indonesia) data, which is an institution that assesses whether a building is qualified to be categorized as a green building with a rating system called greenship which consists of six elements, namely land use, water conservancy, energy effectiveness, air quality, materials used, and environmental management around the building. One of the buildings that successfully obtained a Green Building certificate by GBCI is Pacific Place Mall located in Sudirman Central Business district, Senayan, South Jakarta. The design of this building uses the concept of environmentally friendly buildings through energy saving and greening. This study aims to analyze in more detail related to the things that make Pacific Place Mall included in the Green Building criteria. The data collection technique of this research uses qualitative methods, namely by collecting data through literature, direct observation to the field, and analyzing principles in accordance with the concept of Green Architecture. The findings in this study are that the Pacific Place Mall building has used six aspects of greenship, namely land use, water conservancy, energy effectiveness, air quality, materials used, and environmental management around the building